Evaluación de la producción de biogás a partir de estiércol vacuno recolectado en la finca la carbonera (2020)
This project is developed in order to evaluate the economic potential of biogas produced from the available manure in the “La Carbonera” farm; In order to carry out the process, three experimental phases are implemented, the first one identifies the environmental conditions of the area and determines the state of the manure generation, as the physicochemical characteristics of the raw material, and the second contemplates the implementation of a system of biodigesters that allow to carry out a fermentation. In the third one, the biogas produced is quantified and the methane content is evaluated by means of a gas chromatography analysis according to the results of the first phase and the availability of residues in the farm. A multistage system of biodigesters of 25 L is proposed that allows to control the critical variables of the process such as pH and temperature separately for each phase of biodigestion, with polystyrene insulators in order to reduce heat losses from reactors towards the surroundings in order to maintain a constant temperature that allows the production of biogas, taking into account the bibliographic sources consulted and the environmental conditions. When the hydrolytic-acidogenic stages such as the acetogenic-methanogenic stages are controlled separately, it is possible to carry out the process in an optimal way favoring the results in the production of the final product of interest.